The Collective Remembrance of Chŏng Mong-ju’s Biography – The Samgang Haengsil-to Versions (Politeja, 2025)
This paper examines the portrayal of Chŏng Mong-ju’s assassination in the Samgang haengsil-to (Illustrated Guide to the Three Relationships), one of the earliest texts intended for a broader, common audience due to its use of vernacular script. As a prominent philosopher and politician of the late Koryŏ period, Chŏng Mong-ju’s death became a symbolic turning point in the founding of the Chosŏn dynasty, despite his staunch opposition to it. This study explores how the narrative of his assassination was woven into the foundational myth of Chosŏn and traces the shifts in responsibility and blame for his death as the dynasty evolved. Through an analysis of these early sources, the study aims to uncover how this pivotal event was presented to the populace in comparison with other official sources and contemporary interpretations.